Evaluating the effect of seasonal conditions on metabolism and photosynthetic performance of Picochlorum sp. and its influence on biomass productivity. (June 2022) - Manjre, Suvarna; Paul, Kenny; Patil, Smita; Pai, Puja; Banerjee, Arun; Sarkar, Purbasha; Teredesai, Aniket; Shukla, Manish R.; Dasgupta, Santanu
Abstract: Microalgae productivity is majorly influenced by changing seasonal conditions affecting its micromorphology, physiology and metabolic activity. In this study, microalga belonging to the Picochlorum sp. isolated from tropical habitat was found to be better adapted and twice as productive in the summer tropical simulations compared to winter. Reduced growth in winter was metabolically corroborated by an increase in carbon squandering pathways in winter simulating conditions through the upregulation of photorespiratory pathway and 2-fold increase in biomass accumulation in summer simulation through the upregulation of carbon conserving pathways. Ultrastructural studies revealed increased thylakoid membrane space in winter simulation compared to summer simulating conditions affecting diffusion and metabolite distribution. Furthermore, reduction in photosystem II electron transport rate with nearly half the performance index was observed in winter. This study narrows down the possible metabolic, physiological, and ultrastructural changes at seasonal abiotic variations critically affecting the microalgae carbon fixation and productivity. Graphical abstract: Unlabelled Image Highlights: Metabolic and physiological factors validated higher productivity in summer. Winter growth conditions upregulated carbon squandering pathways. PSII electron transport rate and PIABS significantly reduced in winter. Light and temperature shift caused perturbation in photosynthetic apparatus. Demonstrated new approach to pinpoint bottlenecks of algae productivity.